The Interplay of Meaning between Verbal and Visual Texts in a Japanese Children’s Book - Dewi Puspitasari (Lingua Cultura, 2021)
The research aimed to interpret the meaning of aspects in the verbal and visual texts to identify whether these two textscreated interplay. It was intended to understand the meaning conveyed by the writer and illustrator in a Japanese children’s book entitled ‘Kuroino’ (Little Shadow). The research used the approaches for verbal text analysis by Halliday about Systemic Functional Linguistics (SFL), and visual text analysis by Kress and van Leeuwen about Visual Grammar (VG). The research method was descriptive qualitative by explaining two data types: clauses in the Japanese language and images in the storybook. The data analysis of every aspect in the three metafunctions of language and the three metafunctions of images show the meaning that completes each other. In the analysis of ideational meaning, interpersonal meaning, and textual meaning, the writer narrates the friendship and adventure of ‘Kuroino’ (the Black) and Watashi (I). Meanwhile, in the analysis of representational meaning, interactive meaning, and compositional meaning, the illustrator describes two characters in a book entitled ‘Kuroino’ as the focuses in some pictures. Besides, the illustrator describes the background in detail as if he invites the reader to participate in the adventure of these two characters. Although verbal and visual texts describe a story from two different perspectives, in ‘Kuroino’, these texts collaborate to create a message in the story with synergy and meaning to be easily understood by the readers by maintaining the entertainment aspect in a story narrated.